2013
DOI: 10.1111/ppl.12064
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of the V‐ATPase subunit c and V‐PPase isoforms in Cucumis sativus under heavy metal stress

Abstract: Two electrogenic proton pumps, vacuolar H(+) transporting ATPase (V-ATPase, EC 3.6.3.14) and vacuolar H(+) transporting inorganic pyrophosphatase (V-PPase, EC 3.6.1.1), co-exist in the vacuolar membrane of plant cells. In this work, all CsVHA and CsVHP genes encoding V-ATPase and V-PPase, respectively, were identified in the cucumber genome. Among them, three CsVHA-c genes for V-ATPase subunit c and two CsVHP1 genes for type I V-PPase were analyzed in detail. Individual isogenes were differentially regulated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 54 publications
0
27
0
Order By: Relevance
“…Recently, Kabala et al . () demonstrated differential transcriptional responses of three isoforms (CsVHA‐c1, CsVHA‐c2 and CsVHA‐c3) of the subunit c of V‐ATPase in Cucumis sativus under HM stress. Thus, the transcript amounts of CsVHA‐c1 increased due to a 24 h Cu and Ni treatment and those of CsVHA‐c3 due to Ni only.…”
Section: Responses Of Vacuolar H+ Pumps To Toxic Hm Ionsmentioning
confidence: 97%
See 2 more Smart Citations
“…Recently, Kabala et al . () demonstrated differential transcriptional responses of three isoforms (CsVHA‐c1, CsVHA‐c2 and CsVHA‐c3) of the subunit c of V‐ATPase in Cucumis sativus under HM stress. Thus, the transcript amounts of CsVHA‐c1 increased due to a 24 h Cu and Ni treatment and those of CsVHA‐c3 due to Ni only.…”
Section: Responses Of Vacuolar H+ Pumps To Toxic Hm Ionsmentioning
confidence: 97%
“…sativus roots points to a role of CsVHP1 ; 1 under Cu stress (Kabala et al . ). As in the case of VHA‐a, the V‐PPase mRNA levels were increased in shoots of A .…”
Section: Responses Of Vacuolar H+ Pumps To Toxic Hm Ionsmentioning
confidence: 97%
See 1 more Smart Citation
“…V-ATPase and V-PPase are two tonoplast proton pumps for translocating H + into the vacuoles to generate a gradient of H + , which provide a driving force for the accumulation of ions and other solutes in the vacuole. Their functions in plant abiotic stress tolerance have been widely discussed [187,188]. For example, an M .…”
Section: Membrane Traffickingmentioning
confidence: 99%
“…In plant, there are three distinct membrane H + -pumps that can generate pH gradients: the P-type (H + )-ATPase in plasma membrane to export H + from cells (Serrano, 1993); the vacuolar (H + )-ATPase (V-ATPase) complexes that are encoded by ≥ 26 genes and can acidify vacuoles and other intracellular trafficking compartments (Strompen et al, 2005); and the vacuolar (H + )-PPases (VPs) that are single subunit proteins and can generate H + gradients in endomembrane compartments using PPi (Zhen et al, 1997). Expression of the VP gene can be upregulated by various abiotic stresses, including low nutrient, drought, cold, heat, heavy metal and salinity stresses (Gaxiola et al, 2001;Han et al, 2005;Queiros et al, 2009;Kabala et al, 2014;Wehner et al, 2015;Graus et al, 2018). Previous studies have shown that overexpression of VP genes can enhance drought and/or salinity stress tolerance in plants, including Arabidopsis thaliana, Suaeda salsa, wheat (Triticum aestivum) and Nicotiana benthamiana (Gaxiola et al, 2001;Gao et al, 2006;Guo et al, 2006;Brini et al, 2007;Graus et al, 2018).…”
Section: Introductionmentioning
confidence: 99%